The Wild Garden : A Complete Illustrated Guide to Creating a Garden Using Wild and Native Plants - Stevenson, Violet (London Frances Lincoln, 1987)
An informative book which reflects the concern with conservation and the environment. It shows how to create a natural garden using wild and native plants. The author also wrote "A Garden Full of Flowers", "Dried Flowers for Decoration", "Flower Craft" and "The Encyclopaedia of Flristry".
Include Index, Appendix and Illustration
Keywords: Wild flower gardening -- Landscape gardening -- Native plant gardening